OpenOpticalFlow_PIV: An Open Source Program Integrating Optical Flow Method with Cross-Correlation Method for Particle Image Velocimetry. (5th February 2021) - Liu, Tianshu; Salazar, David M.
This paper describes OpenOpticalFlow_PIV, an open source Matlab program integrating the optical flow method with the cross-correlation method for extraction of high-resolution velocity fields from particle images with large displacements. This hybrid method provides an additional tool to process PIV images, which combines the advantages of the optical flow method and cross-correlation method and overcomes the intrinsic issues of the two methods. The principles of the hybrid method are concisely described, including the cross-correlation method for initial coarse-grained estimation and the optical flow method for refined high-resolution estimation. This paper gives more detailed descriptions of the main program, relevant subroutines and selection of the relevant parameters for computation. Examples are given to demonstrate applications of the hybrid method.